Comparing the Roles of Ambiguity and Unpredictability in Intolerance of Uncertainty. Issue 1 (4th March 2015) - Byrne, Simon Patrick; Hunt, Caroline Jane; Chang, Betty P. I.
<x content-type="archive" xml:space="preserve">Abstract</x> One means by which Intolerance of Uncertainty (IU) purports to contribute to anxiety is by increasing Threat Perception (TP). This process was examined by comparing two different definitions of uncertainty: ambiguity versus unpredictability. N = 104 participants were measured for IU and then made worry and TP estimates for four different scenario types: Ambiguous Scenarios (where an outcome could be interpreted as threatening), Unpredictable Positive Scenarios (where a surprising and positive outcome was anticipated), as well as Positive and Negative Scenarios (with certain outcome). Both Ambiguous and Unpredictable Positive Scenarios more strongly predicted the relationship between IU and worry scores than (certain) Positive or Negative Scenarios. The relationship between IU and 'ambiguous worry' was largely explained by TP estimates, whereas the relationship between IU and 'Unpredictable Positive Worry' was largely independent of TP. Results suggest ambiguity and unpredictability are differentially explained by TP such that they produce different types of response. The authors argue ambiguity and unpredictability are explanatory components within IU.